UTILIZATION OF CORN COB ASH AGRICULTURAL WASTE TO IMPROVE THE PERFORMANCE OF SELF-COMPECTING CONCRETE (SCC) ON COMPRESSIVE STRENGTH AND FLOWABILITY IN MUARA TAMI DISTRICT, JAYAPURA CITY - Harsan Ingot Hasudungan Harsan (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2025)
Utilization of agricultural waste corn cob ash as an admixture or partial cement substitute in self-compecting concrete (SCC) concrete mixtures. Burned corn cobs produce ash with silica content that has the potential as a pozzolan material. This waste is widely produced by farmers in Muara Tami District, Jayapura City, but has not been optimally utilized. This study aims to evaluate the effect of corn cob ash on two main aspects of SCC concrete, namely compressive strength and flowability. The methodology used includes making concrete mixtures with varying levels of corn cob ash of 0%, 5%, 10%, 15%, 20% as a partial cement substitute, followed by laboratory tests on the mechanical properties and workability of the concrete. Based on the test results, it can be concluded that the SCC concrete mixture with the addition of corn stalk ash (ABJ) up to 15% is still classified as normal SCC concrete based on the slump flow test, while the 20% ABJ mixture shows rather stiff properties and is less ideal for use as SCC concrete. The T500 flowability test shows that all mixtures, from 0% ABJ to 20% ABJ, have a spread time that is still within the normal range, namely between 2.5 and 4.9 seconds, thus meeting the flowability criteria for SCC concrete. In terms of compressive strength, the 5% ABJ mixture gives the best results, namely 36.6 MPa at 7 days and 48.9 MPa at 28 days, making it the most recommended mixture for use in SCC concrete structures. Conversely, the 20% ABJ mixture shows a significant decrease in compressive strength, making it less suitable for structural applications. Keywords: Self-compacting concrete (SCC); Corncob Ash; Slum Flow; Flowability; Compressive Strength